E-LKPD based on Problem-Based Learning on Physical Quantity Measurements to Improve Decision-Making Skills - Nur Khoiri (Yayasan Keluarga Guru Mandiri, 2023)
The development of digital learning media as problem-based E-LKPD (electronic LKPD) has become a significant trend in the education sector. This media utilizes information and communication technology to provide students with a more interactive, interesting, and relevant learning experience. Nonetheless, it is crucial to determine the extent to which this media contributes to decision-making. Therefore, this research aims to determine the effectiveness of PBL-based electronic LKPD on physical quantity measurement to improve decision-making skills. This research was quasi-experimental with a one-group pretest-posttest design. The research subjects were 25 10th-grade students. The research instrument was a physical quantity measurement test containing decision-making skills. Effectiveness was measured using the N-Gain test. The research results show that the effectiveness of E-LKPD is in the high category. Moreover, this research reveals that decision-making skills can be trained using problem-based E-LKPD. Furthermore, the results of this research can be developed for other physics topics. This study could assist in the following four domains: curriculum design, learning resource development, continuing professional development for teachers, and integrating technology into the classroom.